Teaching English to the Students at Remote School (Implementation of Fun English Learning in Enhancing Students’ Vocabulary at SMP 1 Limbong) - Paldy Paldy; Sri Rahayu (Universitas Cokroaminoto Palopo, 2014)
The aims of this research are to what extent the implementation of fun English learning in enhancing students’ vocabulary and to find out students’ interest toward the implementation of Fun English Learning to the students at remote school at Limbong. The students are thought in indoor class and outdoor class by applying fun English learning. The researcher used experimental research design, which applies pretest and post-test. The researcher will use two instruments namely vocabulary test and interview. The population of this research is the students at SMP 1 Limbong. There are 98 students was taken from three classes that are class 7, 8, and 9. The researcher will choose the eighth grade students, which consists of 20 students as sample. The results of this research are; 1) the used of fun English learning in teaching vocabulary improved the students’ achievement, 2) the students are interest in learning English by applying fun English learning, Most of them gave positive responses.